Spectroscopic characterization of N,N-bis(2-{[(2,2-dimethyl-1,3-dioxolan-4-yl)methyl]amino}ethyl) N?,N?-dihydroxyethanediimidamide and its complexes - Canpolat, E; Kaya, M (Maik Nauka/Interperiodica, 2005)
A new dioxime ligand, N,N-bis(2-{[(2,2-dimethyl-1,3-dioxolan-4-yl)methyl]amino}ethyl)N',N'-dihydroxyethanediimidamide (H2L), and its mononuclear complexes with Co2+, Ni2+, Cu2+, Zn2+ and Cd2+ are synthesized. H2L forms transition metal complexes [Co(LH)(2)(H2O)(2)] and [M(LH)(2)] (M = Ni2+, Cu2+) with a metal : ligand ratio of 1 : 2. Complexes [M(H2L)(Cl)(2)] (Zn2+, Cd2+) have a metal : ligand ratio of 1 : 1. The mononuclear Co2+, Ni2+, and Cu2+ complexes indicate that the metal ions coordinate ligand through its two N atoms, as the most of dioximes. In the Co2+ complex, two water molecules and in the Zn2+ and Cd2+ complexes two chloride ions are also coordinated to the metal ion. The structures of these compounds are identified by elemental analyses, IR, H-1 and C-13 NMR, electronic spectra, magnetic susceptibility measurements, conductivity, and thermogravimetric analysis.
Keywords: Transition-Metal-Complexes; Vic-Dioxime; Crystal-Structure; Reactivity; Ni(Ii); Cu(Ii); Oxime; Copper(Ii); Ligands; Zn(Ii)